Terra: la biofilia como estrategia de diseño para promover la relación entre el hombre y la naturaleza en espacios educativos para la primera infancia (2023)
The little relationship with nature in educational spaces that influences the cognitive development of early childhood, which acts in the transmission of stimuli, where the absence of nature shows a lower performance in multiple aspects of development, intellectual, emotional, social, spiritual and physical. An educational equipment for early childhood is proposed, which seeks to promote the relationship between nature and the human being, based on the values ​​and patterns of biophilic design, which will positively influence the cognitive, intellectual, emotional and physical development of the first child. childhood.